PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP KINERJA BILLER DENGAN MOTIVASI EKSTRINSIK SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN SANOBAR GUNAJAYA - Ihsan, M Nasrul; Tanjung, Hasrudi; Pasaribu, Fajar (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2024)
This study aims to identify and analyze the effect of workload and remuneration on plaintiff performance moderated by extrinsic motivation at Sanobar Gunajaya Company. The sample in this study was a saturated sample in which the entire population was surveyed, but supervisors were not included in the sample. Although this research sample consists of 74 plaintiffs, this type of research is quantitative and uses SEM-PLS statistical analysis. This study used the SmartPLS 4 software program for data processing. The data were analyzed using a quantitative approach with statistical analysis, namely the Partial Least Squares Structural Equality Model (PLS-SEM). The results of this study prove that workload has a positive and significant influence on plaintiff performance. Compensation has a small positive impact on claimant performance. Extrinsic motivation does not reduce the impact of workload on plaintiff performance. Extrinsic motivation does not moderate the impact of rewards on claimant performance.